The miraculous year 2010 in United States' gay rights law: Anomaly or tipping point? - Arthur S Leonard (Amsterdam Law Forum, 2011)
During 2010 a series of decisions by United States District Court judges appeared to mark a significant breakthrough in the ongoing struggle by sexual minorities in the United States to achieve legal equality through the removal of objectionable laws and policies. Almost as if a dam had broken, there was a sudden rush of developments on three highly contested fronts: (1) the statutory ban on military service by openly gay individuals, (2) the exclusion from federal recognition for lawfully contracted same-sex marriages, and (3) a popularly enacted California state constitutional amendment taking away same-sex marriage rights that had previously been granted by a state supreme court decision. In each of these cases, the district courts declared the contested policy to be unconstitutional and ordered injunctive relief, placing in doubt the willingness of courts to continue crediting traditional arguments that had been successfully invoked by the government when defending these and similar policies in past cases. In this comment, the author argues that these decisions may work a fundamental change in the analysis of LGBT constitutional claims that portends significant progress towards achieving legal equality for sexual minorities in the United States.